Vol 17 No 1 (2023) Pengaruh Sistem Informasi Akuntansi, Motivasi Kerja, Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT Yummy Corp Hub Kemang - Gugum Zulkarnain Ishaq Gugum Zulkarnain Ishaq; Safrudin Safrudin; Achmad Jaelani Achmad Jaelani (LPPM Swadaya Institute of Business and Communication, 2023)
The purpose of this study was to test whether the Accounting Information System, Work Motivations and Leadership Style at PT. Yummy Corp Hub Kemang can affect Employee Performance. This type of research uses quantitative methods. The quantitative method is to emphasize the analysis of numerical data (numbers) processed by statistical methods. The population in this study were all employees workingat PT. Yummy Corp Hub Kemang in 2021 totaling 80 people. Sampling uses a purposive sampling method, which is a sampling approach based on researchers' consideration and has a relevance to the character of the population. The criteria used in this sampling are employees who work as Accounting Staff, Finance, SPV (Supervisor) Storage, and Administrative Staff, so the sample size is 59 people. Data analysis techniques used are description statistics, data validity and reliability, classical assumptions, multiple linear regression, correlation coefficients, coefficient of determination, partial test and simultaneuo tests using the IBM SPSS 21 application. The results of this study indicate that partially Accounting Information Systems and Work Motivations significantly influence Employee Performance. While the Leadership Style does not significantly influence Employee Performance. Simultaneously or simultaneously Accounting Information Systems, Work Motivations, and Leadership Styles have a significant effect on Employee Performance.